Silver Nanowire Electrodes: Conductivity Improvement Without Post-treatment and Application in Capacitive Pressure Sensors - Wang, Jun; Jiu, Jinting; Araki, Teppei; Nogi, Masaya; Sugahara, Tohru; Nagao, Shijo; Koga, Hirotaka; He, Peng; Suganuma, Katsuaki (Nano-Micro Letters, 2014)
Transparent electrode based on silver nanowires (AgNWs) emerges as an outstanding alternative of indium tin oxide film especially for flexible electronics. However, the conductivity of AgNWs transparent electrode is still dramatically limited by the contact resistance between nanowires at high transmittance. Polyvinylpyrrolidone (PVP) layer adsorbed on the nanowire surface acts as an electrically insulating barrier at wire–wire junctions, and some devastating post-treatment methods are proposed to reduce or eliminate PVP layer, which usually limit the application of the substrates susceptible to heat or pressure and burden the fabrication with high-cost, time-consuming, or inefficient processes. In this work, a simple and rapid pre-treatment washing method was proposed to reduce the thickness of PVP layer from 13.19 to 0.96 nm and improve the contact between wires. AgNW electrodes with sheet resistances of 15.6 and 204 Ω sq−1 have been achieved at transmittances of 90 and 97.5 %, respectively. This method avoided any post-treatments and popularized the application of high-performance AgNW transparent electrode on more substrates. The improved AgNWs were successfully employed in a capacitive pressure sensor with high transparency, sensitivity, and reproducibility.